How do you prove #sintheta=+-tantheta/(sqrt(1+tan^2theta))#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Bdub Share
Mar 8, 2018

Answer:

See Below

Explanation:

#RHS: +-tan theta/(sqrt(1+tan^2theta))#

#=+-tan theta/sqrt(sec^2theta)#

#=tan theta/sec theta#->since we are squaring #sectheta# the result is always positive so we drop the negative sign.

#=(sin theta/cos theta)/(1/costheta)#

#=sin theta/cancelcos theta * cancelcos theta/1#

#=sin theta#

#=LHS#

Was this helpful? Let the contributor know!
1500
Impact of this question
62 views around the world
You can reuse this answer
Creative Commons License